Po svodkam MVD . Po svodkam MVD . The Ministry of Internal Affairs' Reports . По сводкам МВД - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Vasilii Trushin, USSR Deputy Internal Affairs Minister, talks about the rising crime rate in the USSR, and his ministry's efforts to combat it. Featured in the program: Trushin, Vasilii (First Deputy Minister of Internal Affairs of the USSR) Первый заместитель министра внутренних дел СССР Василий Трушин рассказывает о росте преступности в СССР и методах борьбы с правонарушениями. В программе участвуют: Трушин, Василий (Первый заместитель министра внутренних дел СССР)